The Influence of Quality Academic Service on Student Satisfaction (Empiric Study on Bidikmisi Scholarship Students Regional Office of Universitas Terbuka at Pangkalpinang, Indonesia) - Mr Yusuf (Integrated Journal of Business and Economics (IJBE), 2018)
This study aims to analyze the influence of the quality of academic service to the satisfaction student regional office of Universitas Terbuka (UPBJJ-UT) Pangkalpinang. The research method used is survey method. Type of research that is verification and descriptive. Data collection conducted through interviews and distribution of questionnaires. Multiple linear regression test obtained Y = 0,629 + 0,237X1 + 0,224X2 + 0,366X3 + 0,254X4 + 0,506X5 + E, multiple correlation test obtained (R) 0,919 and determination coefficient (R2) 84,5% and the rest (E) 15,5% influenced by other factors that are not examined the author. The value of F- count is greater than F-table (101,049>2,31), so it is stated that there is the significant hypothesis. It can be concluded that the quality of service simultaneously has a positive and significant effect on student satisfaction. Partially tangibles, empathy, reliability, responsiveness, assurance have the positive and significant effect on student's satisfaction at UPBJJ-UT Pangkalpinang.